The impact of music on the bioelectrical oscillations of the brain - Kučikienė, Domantė; Praninskienė, Rūta (Acta medica Lituanica, 2018)
In this article we conclude the main scientific studies into the changes in the bioelectrical brainwave activity that occur while listening to music. A brainwave spectral analysis, derived from findings of electroencephalograms, is a powerful tool to obtain deep and objective insights into the effects of music on the brain. This capacity is being investigated in various contexts. Starting with a healthy population, studies also seek to determine the impact of music in such conditions as disorders of consciousness, psychiatric diseases, and chronic conditions, as well as to further explore the role of music for rehabilitation purposes. Supplemental investigations in this field are needed not only to deepen the knowledge of general neurophysiology of listening to music, but also to possibly open new perspectives for its broader use in clinical practices.